THE APPLICATION OF PROJECT BASED LEARNING MODEL (PjBL) TO INCREASE student’ ACCURACY AND CREATION IN ART - Ferdi Efrimal; Nina Kurniah; Wasidi Wasidi (UNIB Press, 2017)
The purpose of this research is to describe, the first application of project based learning model can improve students' accuracy in art learning, the two application of project based learning model can improve student's art creations and the three effective the implementation of project based learning model to improve art creations. This research used Classroom Action Research (PTK) and to know the effectiveness of Learning Based Learning model was conducted by using Quasi Experimental research model. The data were collected by observation and test. The subjetc of Classroom Action Research Subjects was class XI IPS students 1. The experimental class and control class were choosen by pairing the students of class XI IPS 2 as experimental class and the students of class XI IPS 3 as control class. The result of this research can be concluded that the application of Project Based Learning model can improve the students' accuracy and creative arts. application of Project Based Learning model) efektif can improve art creations in SMA Negeri 3 Seluma. Keywords: learning model project based learning, meticulousness, creative art